As long as grandmothers talk...: A sociolinguistic approach to bilingualism in an Almopian village - Drettas, Georges (The Greek Review of Social Research, 1981)
First of all the author briefly describes the make-up of societal bi lingualism of a rural settlement in Almopia He then examines the phonetic components of the native local accent, paying particular at tention to the semiotic use of the accent of this multi-lingual area (recognition between speakers and stylistic interplay in speech). Finally, this brief description ends with a series of hypothesis about the maintenance of the local language up today.